High cardiovascular disease mortality after penile squamous cell carcinomas diagnosis: Results from the United States SEER population, 2005-2016 - Xie, Zequan; Zhan, Xiangpeng; Zheng, Yunwei; Liu, Yang; Chen, Tao; Jiang, Ming; Li, Yu; Fu, Bin (Frontiers in Oncology, 2022)
Background Cancer survivorship care is an emerging and necessary component of oncology management. To explore cardiovascular disease (CVD)-specific mortality and prognostic factors among patients with penile squamous cell carcinomas (PSCC). These results aid clinicians in furtherly understand this disease’s prognosis. Method We analyzed Surveillance, Epidemiology and End Results Program data for 2668 PSCC cases diagnosed between 2005 to 2016. We calculated standardized mortality ratios (SMRs) of CVD and all-cause mortality, comparing PSCC patients with general population men. A cumulative mortality curve and competitive risk regression model were utilized to evaluate the prognostic factors of CVD-specific death. Results Death distribution is as follows: PSCC (42.4%), other causes (21.3%) CVD (19%), and other cancers (17.3%). PSCC patients are more like to die from CVD (SMR=3.2, 95%CI: 3.1-3.3) and all-cause death compared with the general population. Meanwhile, patients undergoing surgery show a relatively higher CVD-specific mortality than the general population (SMR=2.7, 95%CI: 2.4-3.2). In the competitive risk model, higher CVD mortality is associated with age, region, year of diagnosis, stage, and marital status (all P<0.05). Patients with the localized stage show a higher risk of CVD-specific death than those with regional or distant stage. Conclusion Our study mainly reveals that cardiovascular disease was the important cause of death and higher CVD-specific mortality among PSCC patients. Several associated factors related to CVD-specific death are also identified. In the future, more work in educating health care professionals on the components of survivorship care is needed to meet the long-term and late effects cancer patients experience.